IMPLEMENTASI SISTEM PENJAMINAN MUTU INTERNAL (SPMI) DALAM PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH ATAS SWASTA (SMAS) TAHFIDZ AL QURAN WAHDAH ISLAMIYAH ANABANUA - Hasnidar, Hasnidar; Darmawan, Darmawan; Muhammad Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Internal Quality Assurance System (IQAS) in improving the quality of education based on spiritual aspects, particularly students’ responsibility and discipline at SMAS Tahfidz Al Quran Wahdah Islamiyah Anabanua. This research employs a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation involving the principal, teachers, and students as research informants. The results show that the implementation of IQAS has been carried out through the PPEPP cycle (Determination, Implementation, Evaluation, Control, and Improvement) in a systematic and continuous manner. At the determination stage, the school sets quality standards not only in academic aspects but also in spiritual dimensions as a distinctive characteristic of Islamic educational institutions. At the implementation stage, spiritual values are integrated into school activities such as Quran memorization programs, daily worship practices, moral habituation, and character development of students consistently. The evaluation and control stages are conducted periodically through activity monitoring and assessment of students’ attitudes. The evaluation results are then used as the basis for continuous improvement to enhance program effectiveness. Supporting factors include visionary school leadership, active teacher involvement, and a strong religious school culture. Meanwhile, inhibiting factors include limited understanding of IQAS among school members and limited supporting resources. Overall, the implementation of IQAS contributes significantly to improving educational quality, both academically and spiritually, and in shaping disciplined, responsible, and morally upright students in daily life, while strengthening a sustainable and comprehensive quality culture based on Islamic values.